2020
DOI: 10.1186/s12870-020-02569-z
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic profiling of germinating seeds under cold stress and characterization of the cold-tolerant gene LTG5 in rice

Abstract: Background: Low temperature is a limiting factor of rice productivity and geographical distribution. Wild rice (Oryza rufipogon Griff.) is an important germplasm resource for rice improvement. It has superior tolerance to many abiotic stresses, including cold stress, but little is known about the mechanism underlying its resistance to cold. Results: This study elucidated the molecular genetic mechanisms of wild rice in tolerating low temperature. Comprehensive transcriptome profiles of two rice genotypes (cold… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(29 citation statements)
references
References 59 publications
(77 reference statements)
0
29
0
Order By: Relevance
“…Comparative transcriptome profiling can provide millions of treatment-dependent reads that can be aligned with reference genomes (if available) and de novo (if not) and ultimately will provide thousands of novel transcripts/genes. For example, in rice, mRNA sequencing of two contrasting cultivars, i.e., Y12–4 (cold-tolerant) and 253 (cold-sensitive) showed that a total of 42.44–68.71 million reads were obtained and later on aligned to nearly 30 and 29 thousand genes, respectively [ 93 ]. In the results, a majority of cold tolerant DEGs were found in tolerant genotype.…”
Section: Membrane Transporters and Abiotic Stressesmentioning
confidence: 99%
“…Comparative transcriptome profiling can provide millions of treatment-dependent reads that can be aligned with reference genomes (if available) and de novo (if not) and ultimately will provide thousands of novel transcripts/genes. For example, in rice, mRNA sequencing of two contrasting cultivars, i.e., Y12–4 (cold-tolerant) and 253 (cold-sensitive) showed that a total of 42.44–68.71 million reads were obtained and later on aligned to nearly 30 and 29 thousand genes, respectively [ 93 ]. In the results, a majority of cold tolerant DEGs were found in tolerant genotype.…”
Section: Membrane Transporters and Abiotic Stressesmentioning
confidence: 99%
“…Transcriptomic analysis has been a highly efficient way to reveal cold-responsive genes in many crops, such as maize ( Li et al, 2019 ), rice ( Pan et al, 2020 ), Brassica napus ( Mehmood et al, 2021 ) and Brassica juncea ( Sinha et al, 2015 ). Microarray analysis of peanut leaves subjected to low temperature got a number of cold-regulated genes and provided some useful insights into cold signal transduction pathways in peanut ( Chen et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have been published to show the effectiveness of transcriptome analysis in identification of new genes or regulatory pathways for plant response to low temperature stress [ 18 , 19 ]. By comparing cold-responsive transcriptomes of wild type and mutants or cultivars of contrasting cold tolerance, a number of genes involved in multiple biology processes, such as cell cycle, zeatin biosynthesis, hormone signal transduction, membrane part, and response stimulus, have been found to be regulated by cold stress in rice [ 20 , 21 , 22 ]. When cold stress was imposed on seedlings of maize, numerous cold-stress-related genes were also identified, and these genes fall into similar functional categories as rice research indicated [ 1 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%